2022
DOI: 10.1371/journal.ppat.1010765
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal autolysin promotes dysfunction of swine tracheal epithelium by interacting with vimentin

Abstract: Streptococcus suis serotype 2 (SS2) is a major zoonotic pathogen resulting in manifestations as pneumonia and septic shock. The upper respiratory tract is typically thought to be the main colonization and entry site of SS2 in pigs, but the mechanism through which it penetrates the respiratory barrier is still unclear. In this study, a mutant with low invasive potential to swine tracheal epithelial cells (STECs) was screened from the TnYLB-1 transposon insertion mutant library of SS2, and the interrupted gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…SS2 can cause systemic infection through the swine respiratory tract [ 17 ]. Excessive inflammation and increased permeability of the airway epithelial barrier are the major pathophysiological events during SS2 infection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SS2 can cause systemic infection through the swine respiratory tract [ 17 ]. Excessive inflammation and increased permeability of the airway epithelial barrier are the major pathophysiological events during SS2 infection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inflammation and increased permeability of the airway epithelial barrier are the major pathophysiological events during SS2 infection [ 32 ]. Given that the ability of SS2 to penetrate the tracheal epithelium of vimentin null mice and enter various tissues was markedly reduced [ 17 ], we hypothesize that vimentin is involved in SS2-induced excessive inflammatory response. Here, we found that vimentin contributed to lung damage, the number of neutrophils and expression of proinflammatory cytokines and chemokines in the lungs of mice and STEC after SS2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations